Time Zone Unknown Artists' Development Iniciative collaborating with Wayne McGregor, a diary - Bull, Deborah (Dance Books Ltd., Alton,Hampshire (UK), 2001)
Wayne McGregor, Random and the Artists' Development Iniciative, a diary. PALABRAS CLAVE: Wayne McGregor, Artists' Development Iniciative, Symbiont(s), Random, Duo:logue, Aeon, brainstate, Royal Ballet dancers.